Семантико-синтаксичні реченнєві відношення і синтаксичні зв’язки (на матеріалі поезій Тараса Шевченка) - Масицька, Тетяна; Masytska, Tetayna (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті досліджено функційні особливості семантико-синтаксичних реченнєвих відношень і синтаксичних зв’язків. Указано, що в граматичній структурі українського речення функціонують семантико-синтаксичні відношення, які формують семантико-синтаксичний аспект речення, і синтаксичні зв’язки, які характеризують формально-синтаксичний аспект реченнєвої структури. Виділення основних типів семантико-синтаксичних відношень і синтаксичних зв’язків пов’язане з напрямком синтаксичної залежності. З’ясовано, що семантико- синтаксичні відношення репрезентують семантичну залежність, а синтаксичні зв’язки вказують на тип формальної залежності.The article researches some functional peculiarities of semantic and syntactic sentence relations and syntactic links. It is specified that in the grammar structure of an Ukrainian sentence the semantic and syntactic relations forming the semantic and syntactic aspect of a sentence and the syntactic links that are descriptive of the formal syntactic aspect of a sentence structure are in operation. The differentiation of the semantic and syntactic relations has been examined and the subject, object, addressee, instrumental and locative relations have been studied. The semantic and syntactic relations are directed from the dependent component to the subordinating one. The types and forms of syntactic links have been analyzed and their role for modifying sentence members has been underlined. Distinguishing the main types of semantic and syntactic relations and syntactic links is connected with the direction of syntactic dependency. It turns out that the semantic and syntactic relations represent the semantic dependency and syntactic links points to the type of formal dependency.
Keywords: семантико-синтаксичні реченнєві відношення; синтаксичні зв’язки; семантична залежність; формальна залежність; структура речення; semantic and syntactic sentence relations; syntactic links; the semantic dependency; the formal dependency; a sentence structure